Changes of insulin resistance and β-cell function in women with gestational diabetes mellitus and normal pregnant women during mid- and late pregnant period: A case-control study - Wang, Yun-Hui; Wu, Hui-Hua; Ding, Hong; Li, Yan; Wang, Zhen-Hua; Li, Feng; Zhang, Jian-Ping (The journal of obstetrics and gynaecology research, 2013)
Aim The aim of this study was to observe insulin resistance and β‐cell function changes among women diagnosed with gestational impaired glucose tolerance or gestational diabetes mellitus (GDM) in mid‐pregnancy. Material and Methods Sixty‐four pregnant women receiving prenatal care underwent an oral glucose tolerance test at 20–24 weeks of gestation and an insulin release test. The GDM group included 34 pregnant women diagnosed with gestational impaired glucose tolerance or GDM, and the subjects with normal blood glucose were the control group. Insulin resistance and islet β‐cell function changes were observed with the oral glucose tolerance test and insulin release test. Results The homeostatic model assessment‐β levels in late pregnancy were higher than those in mid‐pregnancy for both groups, and the primary time effect was statistically significant. The early insulin secretion index (ΔI30/ΔG30) values in mid‐ and late pregnancy were lower in the GDM group. The values of the area under the curve of blood glucose in mid‐ and late pregnancy were higher in the GDM group than those in the control group. Insulin resistance was higher in GDM patients than in normal pregnant women. Conclusions Insulin resistance was aggravated, and β‐cell's ability to compensate for the increased insulin resistance by modulating insulin secretion was aggravated, as gestational week increased in women with gestational diabetes and normal pregnant women. Insulin resistance in women with GDM is higher than in pregnant women with normal metabolism of glucose.